Practical Game Design - Kramarzewski, Adam; Kramarzewski, Adam; Nucci, Ennio De (Packt Publishing, 2018)
Design accessible and creative games across genres, platforms, and development realitiesAbout This BookImplement the skills and techniques required to work in a professional studioAce the core principles and processes of level design, world building, and storytellingDesign interactive characters that animate the gaming worldWho This Book Is ForWhether you are a student eager to design a game or a junior game designer looking for your first role as a professional, this book will help you with the fundamentals of game design. By focusing on best practices and a pragmatic approach, Practical Game Design provides insights into the arts and crafts from two senior game designers that will interest more seasoned professionals in the game industry.What You Will LearnDefine the scope and structure of a game projectConceptualize a game idea and present it to othersDesign gameplay systems and communicate them clearly and thoroughlyBuild and validate engaging game mechanicsDesign successful business models and prepare your games for live operationsMaster the principles behind level design, worldbuilding and storytellingImprove the quality of a game by playtesting and polishing itIn DetailIf you are looking for an up-to-date and highly applicable guide to game design, then you have come to the right place! Immerse yourself in the fundamentals of game design with this book, written by two highly experienced industry professionals to share their profound insights as well as give valuable advice on creating games across genres and development platforms.Practical Game Design covers the basics of game design one piece at a time. Starting with learning how to conceptualize a game idea and present it to the development team, you will gradually move on to devising a design plan for the whole project and adapting solutions from other games. You will also discover how to produce original game mechanics without relying on existing reference material, and test and eliminate anticipated design risks. You will then design elements that compose the playtime of a game, followed by making game mechanics, content, and interface accessible to all players. You will also find out how to simultaneously ensure that the gameplay mechanics and content are working as intended.As the book reaches its final chapters, you will learn to wrap up a game ahead of its release date, work through the different challenges of designing free-to-play games, and understand how to significantly improve their quality through iteration, polishing and playtesting.Style and approachA practical step by step guide to get you up and running with Game Design from scratch